On the Record Range: Ramin Kazemi - Team, Support (Thai Journal of Mathematics, 2015)
In this paper we consider some distributional properties of record range of a sequence of i.i.d continuous uniform random variables. More precisely, We calculate the entropy of the record range and evaluate it as function of n. Also we calculate the joint probability density function of R_n and R_m via a Markov chain and show that the conditional density of R_n given R_n-1 is independent of n. Finally, We prove some nice equalities related to the moments of the record range.